Early childhood education and human development prospects : are some children disadvantaged? - St. Bernard, Godfrey (2011)
Explores the dynamics of exposure to early childhood care and education programmes among children 3-4 years in Trinidad and Tobago based on data from the 2006 Multiple Indicator Cluster Survey (MICS).